2014
DOI: 10.1186/ar4597
|View full text |Cite
|
Sign up to set email alerts
|

Novel immortal human cell lines reveal subpopulations in the nucleus pulposus

Abstract: IntroductionRelatively little is known about cellular subpopulations in the mature nucleus pulposus (NP). Detailed understanding of the ontogenetic, cellular and molecular characteristics of functional intervertebral disc (IVD) cell populations is pivotal to the successful development of cell replacement therapies and IVD regeneration. In this study, we aimed to investigate whether phenotypically distinct clonal cell lines representing different subpopulations in the human NP could be generated using immortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 72 publications
5
59
0
Order By: Relevance
“…In addition, we find that bFoxf1 and bPax1 are not differentially expressed in the bovine tail IVD. ADAMTS17, SFRP2, COL5A1 and COL12A1 were previously identified as (outer) AF markers compared to NP cells [9]. To test if these marker genes distinguish inner from outer AF tissue, they were evaluated in the bovine tail IVD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we find that bFoxf1 and bPax1 are not differentially expressed in the bovine tail IVD. ADAMTS17, SFRP2, COL5A1 and COL12A1 were previously identified as (outer) AF markers compared to NP cells [9]. To test if these marker genes distinguish inner from outer AF tissue, they were evaluated in the bovine tail IVD.…”
Section: Resultsmentioning
confidence: 99%
“…The AF marker genes ADAMTS17, SFRP2, COL5A1 and COL12A1, previously used for cultured NP and AF cells, could be used to distinguish bovine AF from NP tissue [9]. Few studies have addressed inner and outer AF cell phenotypes [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Cells isolated from degenerated and non-degenerated human discs can differentiate into adipogenic, osteogenic, and chondrogenic lineages, indicating that the IVD may include progenitor cells within its population. [8][9][10][11][12][13][14] In addition, expression of markers associated with progenitors (e.g., Tie2, GD2, Stro-1, Oct3/4, CD105, CD90, and Notch-1) suggests that precursor cell populations might be present within degenerated human discs. 8,9 These findings indicate that degenerated human discs may count on an endogenous regenerative capacity, although the exact nature and origin of the participating cells remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Several research groups have begun to use CA12 as an NP marker. [15][16][17] Thus, we hypothesize that CA12 has a role in NP physiology. Although Power et al 14 found that CA inhibition disrupts pH and leads to lactate accumulation in NP cells, the exact function of CA12 in NP remains unknown.…”
mentioning
confidence: 95%